Foreign Direct Investment and Stock Market Development: Evidence from Asia (Journal of Social Sciences Review, 2025)
This paper examines how foreign direct investment impacts stock market development in the South Asia region. FDI is considered an independent variable, whereas the stock market is considered a dependent variable, while interest rate, exchange rate, and inflation are control variables. The data is collected from World Bank indicators, and stock index data is collected from stock exchange websites of South Asian countries. The twenty-one years of data, beginning in 2001 to 2021, are used for the analysis through STATA software. This study used (OLS) the ordinary least square method, to check the relationship between SMD and FDI in South Asian countries. The results show that foreign direct investment has a positive impact on the development of the stock market. The results of this study give insightful direction for investors, showing that the stock market and FDI are related positively. Governments should think about incorporating environmental concerns and sustainable development goals into their FDI promotion policies.
Keywords: Foreign Direct Investment; Stock Market Development; Interest Rate; Exchange Rate; Inflation